2017
DOI: 10.1310/sci2304-313
|View full text |Cite
|
Sign up to set email alerts
|

Trends, Challenges, and Opportunities Regarding Research in Non-traumatic Spinal Cord Dysfunction

Abstract: Spinal cord dysfunction (SCDys) is caused by heterogeneous health conditions, and the incidence is increasing. Despite the growing interest in rehabilitation research for SCDys, research into SCDys faces many challenges. The objective of this project was to perform a clinical review of changes in SCDys research over the last 4 decades; identify challenges to conducting research in SCDys; and propose opportunities for improving research in SCDys. A triangulation approach was used for obtaining evidence: literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 61 publications
(90 reference statements)
0
19
0
2
Order By: Relevance
“…This study is one of the first population-based studies of relative mortality following NTSCI. The study design targeted individuals that were admitted for first rehabilitation, therefore the portion of individuals that never receive specialized rehabilitation or treatment are less represented [3,5], which can limit the generalizability of results to the entire population with NTSCI. Thus, SMRs of individuals not admitted to specialized care may be even higher.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is one of the first population-based studies of relative mortality following NTSCI. The study design targeted individuals that were admitted for first rehabilitation, therefore the portion of individuals that never receive specialized rehabilitation or treatment are less represented [3,5], which can limit the generalizability of results to the entire population with NTSCI. Thus, SMRs of individuals not admitted to specialized care may be even higher.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although epidemiological evidence for NTSCI is limited, the WHO recently summarized a report which estimated the worldwide incidence to vary between 12 and 76 per million population [2]. However, critical epidemiological indicators, instrumental to informing long-term patient management and health policy-including mortality-remain scarce for NTSCI [3]. While most of the currently available literature focuses on traumatic SCI (TSCI) [4,5], this evidence is often not transposable to NTSCI due to the distinct, often age-related pathologies associated with NTSCI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several recent efforts to address ICD coding for patients with non-traumatic SCI and facilitate case finding and health surveillance for this population nationally and internationally. [14][15][16] This acute post-operative phase of injury management is associated with a Canadian median rehabilitation onset of 26-30 days for those with traumatic injury prior to rehabilitation admission to a tertiary rehabilitation facility. 17,18 Recently published examinations from multiple sites across Canada involving >1000 individuals with traumatic SCI, revealed that median rehabilitation length of stay, is 78-79 days (Interquartile Range 64-68 days).…”
Section: Introductionmentioning
confidence: 99%